Chapter 31: Okra Production in Florida - Eric H. Simonne; William M. Stall; Stephen M. Olson; Susan E. Webb; Aaron J. Palmateer (EDIS)
This document is HS729, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.